If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = 28x + 18 Reorder the terms: 41 = 18 + 28x Solving 41 = 18 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 41 + -28x = 18 + 28x + -28x Combine like terms: 28x + -28x = 0 41 + -28x = 18 + 0 41 + -28x = 18 Add '-41' to each side of the equation. 41 + -41 + -28x = 18 + -41 Combine like terms: 41 + -41 = 0 0 + -28x = 18 + -41 -28x = 18 + -41 Combine like terms: 18 + -41 = -23 -28x = -23 Divide each side by '-28'. x = 0.8214285714 Simplifying x = 0.8214285714
| t^2-6t+7=0 | | -6a-4=7a+11 | | 8x+3+2x+6x+5=180 | | 160/x=7.04 | | m31/3 | | 7d+3=12d | | 2x+5=3x+1-x+7 | | 4x+4y=167 | | -2x/7-x/21-5x/42 | | 89175=x+(.025*x) | | -5=2(-1)+b | | 1=2(-1)+b | | -7U+5(U+5)=9 | | -7U+5(U+5)=4 | | 139=5x+19 | | b-(1)a(3b-6a)= | | -1.4g=7 | | 2x+10=5x+30 | | a+v=h | | -2+n=6 | | x^2+x-12y^2= | | 3t^3-9t^2=0 | | 3(2x+3x)=5(6x-20) | | 6x-2=x+1 | | 7-2(3x-1)=14 | | 12(2k+11)=15 | | 4x+7=5y | | -4+3u=-10 | | x^2+y^2-x-9y-24=0 | | 3(2x+1)=-5x+14 | | z-8=9 | | -3x-4x=7x |